Becoming attack-free further improves health-related quality of life in patients with hereditary angioedema receiving garadacimab - Staubach, Petra; Craig, Timothy J; Fukuda, Tomoo; Aygoren-Pursun, Emel; Hakl, Roman; Braverman, Julia; Lawo, John-Philip; Pollen, Maressa; Nenci, Chiara; Li, Philip H; Farkas, Henriette (Allergy and asthma proceedings, 2025)
Background: Hereditary angioedema (HAE) is associated with substantial health-related quality of life (HRQoL) impairments. Complete disease control and life normalization are key treatment goals. In previous studies, garadacimab prevented HAE attacks with a favorable safety profile and HRQoL improvements. Objective: HRQoL was evaluated in patients with HAE receiving garadacimab stratified by attack-free status. Methods: In the pivotal phase III study (NCT04656418), 39 patients received garadacimab 200 mg subcutaneously once monthly and 25 volume-matched placebo. In the phase III open-label extension (OLE), 90 patients in the garadacimab-naive group (received placebo in previous studies or newly enrolled) and 71 patients in the previous garadacimab exposure group (received garadacimab in previous studies) received garadacimab (NCT04739059). Patients ages ≥ 18 years completed the Angioedema Quality of Life (AE-QoL) questionnaire in both studies; scores were evaluated post hoc by attack-free status. Results: In the pivotal phase III and phase III OLE studies, 62% and 60% of patients, respectively, were attack-free. In the pivotal phase III study, the mean AE-QoL total score improved with garadacimab, from 38.8 (day 1) to 6.6 (month 6) for attack-free patients (n = 19) and to 18.4 for patients with one or more attacks (n = 14) versus a change in mean AE-QoL total score from 43.7 to 40.5 with placebo (n = 20). In the phase III OLE study, the mean AE-QoL total score for patients who were garadacimab naive decreased from 46.2 (day 1) to 8.6 (month 12) for attack-free patients (n = 34) and from 54.5 to 23.5 for patients with one or more attacks (n = 30). For the previous garadacimab exposure group, AE-QoL improvements were maintained from previous studies, regardless of attack-free status. Conclusion: Garadacimab was associated with HRQoL improvement versus run-in in all groups. After garadacimab exposure in previous studies, improvements were maintained in the phase III OLE study. Attack-free patients had the greatest HRQoL improvements, bringing them closer to complete disease control and life normalization.Clinical trials NCT04656418, NCT04739059, www.clinicaltrials.gov.
Keywords: dospělí; průzkumy a dotazníky; Female; Quality of Life; Adult; výsledek terapie; mladý dospělý; Angioedemas, Hereditary; ženské pohlaví; Surveys and Questionnaires; kvalita života; lidé; Treatment Outcome; Male; Aged; Young Adult; lidé středního věku; humanizované monoklonální protilátky; senioři; mužské pohlaví; Antibodies, Monoclonal, Humanized; hereditární angioedémy; Middle Aged; Humans